2011
DOI: 10.3109/00016489.2011.616225
|View full text |Cite
|
Sign up to set email alerts
|

Intra-individual assessment of speech and music perception in cochlear implant users with contralateral Cochlearand MED-ELsystems

Abstract: For all objective tests of music discrimination and speech perception in noise, there were no statistically significant differences between MED-EL and Cochlear CI systems. Subjectively, four subjects thought their MED-EL device was better than their Cochlear device for music appreciation. Four thought that music sounded more natural, less tinny and more reverberant with their MED-EL CI than with their Cochlear CI. One subject rated all these to be equal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 15 publications
0
19
0
Order By: Relevance
“…The two different CI systems were tested sequentially with the other turned off, but no significant differences in the enjoyment of music was found between the two devices. 9 …”
Section: Introductionmentioning
confidence: 99%
“…The two different CI systems were tested sequentially with the other turned off, but no significant differences in the enjoyment of music was found between the two devices. 9 …”
Section: Introductionmentioning
confidence: 99%
“…Attempts to improve music enjoyment have focused on improvements in the CI hardware, the CI software, and the music itself. A study in CI users with a MED-EL device on one side and a Cochlear Nucleus on the other found no significant difference in music enjoyment when either device type was used exclusively (12). Recently, we have shown that the novel strategy of re-engineering the original piece of music by either reducing the complexity of music by decreasing the number of musical instruments or minimizing reverberation can increase music enjoyment (13,14).…”
mentioning
confidence: 97%
“…For reasons previously discussed, validation of a single unified test for musical enjoyment has remained an elusive goal. Previous studies of musical enjoyment have used visual analog scales or discrete 10-point scales and have used a diverse array of rating categories including pleasant-unpleasant, natural-unnatural, rich-tinny, fuller-emptier, sharper-duller, rougher-smoother, and excited-calm (6,8,10,17). In this study, the use of a novel melody and selection of three broad rating metrics served to limit preexisting emotional associations with enjoyment and allow ratings on easily identifiable and relatively common terms of enjoyment.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Harris et al (6) studied six CI users with a MED-EL implant device on one side and Cochlear Nucleus implant device on the other. Each device was tested sequentially, with the other turned off, but no significant differences in the enjoyment of music were found between the two devices.…”
mentioning
confidence: 98%